2017
DOI: 10.1101/202325
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An atlas of genetic variation for linking pathogen-induced cellular traits to human disease

Abstract: Summary 35Genome-wide association studies (GWAS) have identified thousands of genetic variants associated with disease. To facilitate moving from associations to disease mechanisms, we leveraged the role of pathogens in shaping human evolution with the Hi-HOST Phenome Project

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 95 publications
0
29
0
Order By: Relevance
“…These studies have identified regulatory variants related to immune activation that act in cis or in trans (e.g., master regulators detected at IFNB1, IRF2, TLR1, or CR1), which are generally cell context dependent, and have revealed major overlaps between such variants and GWAS hits (see, for example, Kim-Hellmuth et al, 2017;Lee et al, 2014;Pala et al, 2017;Piasecka et al, 2018). These findings suggest that regulatory variation may underlie genetic associations with complex organismal phenotypes, such as infectious or autoimmune diseases (Wang et al, 2018).…”
Section: Individual-and Population-level Variation Of Immune Phenotypesmentioning
confidence: 99%
“…These studies have identified regulatory variants related to immune activation that act in cis or in trans (e.g., master regulators detected at IFNB1, IRF2, TLR1, or CR1), which are generally cell context dependent, and have revealed major overlaps between such variants and GWAS hits (see, for example, Kim-Hellmuth et al, 2017;Lee et al, 2014;Pala et al, 2017;Piasecka et al, 2018). These findings suggest that regulatory variation may underlie genetic associations with complex organismal phenotypes, such as infectious or autoimmune diseases (Wang et al, 2018).…”
Section: Individual-and Population-level Variation Of Immune Phenotypesmentioning
confidence: 99%
“…Recently, immunophenotyping based on the performance of the cells of immune system in in vitro models has been successfully carried out in humans. These cellular immunogenetics studies have identified phenotypic variation in cellular responses which then were linked to genetic variations and cellular mechanisms that control the resistance to bacterial infection in human populations (Ko et al, 2013;Alvarez et al, 2017;Wang et al, 2018). In cattle,…”
Section: Introductionmentioning
confidence: 99%
“…In the reductionist approaches, the interactions of the sub-system with pathogens are examined in a controlled environment. In this approach, the performance of the sub-system is the criterion of classification, instead of the holistic approach that is based on the outcome of infection 8,9 . Due to the fact that the sub-system, i.e.…”
mentioning
confidence: 99%